Kontribusi Peradaban Islam terhadap Peradaban Eropa - Yani, Ahmad (CARITA: Jurnal Sejarah dan Budaya, 2023)
This paper aims to reveal the contribution of Islamic civilization to European civilization by discussing: (1) the process of Islamic civilization entering Europe (2) the influence of Islamic civilization on Europe. The results of this study reveal that Islamic civilization entered Europe in four ways, namely the channel of Islamic civilization which influenced Europe through Spain, Sicily, the Crusades and trade exchanges, but the most important channel in this case was Islamic Spain. Spain is the most important place for Europe to absorb Islamic civilization, both in political, social, economic and civilizational relations between countries. It is a historical fact that Spain has been under Islamic rule for more than seven centuries. European civilization was built from the womb of the historical phase of Islam occupying Spain. Socio-politically, Islam is in a very strong position to expand and civilizationally is in its golden peak. This expansion process was followed by the transfer of science from the Muslims to the Spanish population at that time. The open culture and generous knowledge built by the Muslims at that time made every group, region, or ethnic group very wide open to gain knowledge from the Muslims in Spain, including many Europeans who learned knowledge in various fields from Muslim Spain. , both the sciences 'aqli and science naqli. When they have returned to their respective areas, many have developed this knowledge in mainland Europe. Tulisan ini bertujuan mengungkapkan kontribusi peradaban Islam terhadap peradaban Eropa dengan pembahasan meliputi: (1) proses peradaban Islam masuk ke Eropa (2) pengaruh peradaban Islam terhadap Eropa. Hasil kajian ini terungkap bahwa peradaban Islam masuk di Eropa dengan empat cara yaitu saluran peradaban Islam yang mempengaruhi Eropa melalui Spanyol, Sisilia, Perang Salib maupun pertukaran perniagaan, akan tetapi saluran yang terpenting dalam hal ini adalah Spanyol Islam. Spanyol merupakan tempat yang paling utama bagi Eropa menyerap peradaban Islam, baik dalam hubungan politik, sosial, ekonomi maupun peradaban antar negara. Suatu fakta historis Spanyol selama tujuh abad lebih berada dalam kekuasaan Islam. Peradaban Eropa dibangun dari rahim fase sejarah Islam menduduki Spanyol. Secara sosial politik, Islam dalam posisi yang sangat kuat untuk melakukan ekspansi dan secara peradaban dalam Puncak keemasaannya. Proses ekspansi ini diikuti dengan transfer of sciense dari kaum muslimin ke penduduk Spanyol saat itu. Kebudayaan terbuka dan dermawan ilmu yang dibangun oleh kaum Muslimin saat itu, menjadikan setiap kelompok, daerah, atau suku bangsa sangat terbuka lebar menimba ilmu pengetahuan dari kaum Muslimin di Spanyol, termasuk banyak orang-orang Eropa yang menimba ilmu pengetahuan dalam berbagai bidang dari Muslim Spanyol, baik ilmu-ilmu ‘aqli maupun ilmu naqli. Ketika mereka sudah kembali ke daerah masing-masing banyak yang mengembangkan ilmu pengetahuan tersebut di daratan Eropa.